Kinetic and Mechanistic Studies for the Gas-phase Reaction of Ozone with 2, 3-Dimethyl-2-Butene and 1, 3-Butadiene (Baghdad Science Journal, 2017)
The reactions of ozone with 2,3-Dimethyl-2-Butene (CH3)2C=C(CH3)2 and 1,3-Butadiene CH2=CHCH=CH2 have been investigated under atmospheric conditions at 298±3K in air using both relative and absolute rate techniques, and the measured rate coefficients are found to be in good agreement in both techniques used. The obtained results show the addition of ozone to the double bond in these compounds and how it acts as function of the methyl group substituent situated on the double bond. The yields of all the main products have been determined using FTIR and GC-FID and the product studies of these reactions establish a very good idea for the decomposition pathways for the primary formed compounds (ozonides) and give a good information for the effect of the methyl group on the degradation pathways. The results have been discussed from the view point of their importance in the atmospheric oxidation of these pollutants.